Twenty Years of Health System Reform in Brazil: An Assessment of the Sistema Único de Saúde - Gragnolati, Michele (World Bank, 2015)
It has been over twenty years since the Brazilian Sistema Único de Saúde (Unified Health System or SUS) was formally established by the 1988 Constitution. The impetus for the SUS came in part from rising costs and a crisis in the social security system that preceded the reforms, but also from a broad-based political movement calling for democratization and improved social rights. Building on reforms that started in the 1980s, the SUS was based on three overarching principles: (i) universal access to health services, with health defined as a citizen?s right and an obligation of the state; (ii) equality of access to health care; and (iii) integrality (comprehensiveness) and continuity of care; along with several other guiding ideas, including decentralization, increased participation, and evidence-based prioritization.